2003
DOI: 10.7326/0003-4819-138-10-200305200-00006
|View full text |Cite
|
Sign up to set email alerts
|

A Diagnostic Strategy Involving a Quantitative Latex d-Dimer Assay Reliably Excludes Deep Venous Thrombosis

Abstract: A negative result on a quantitative latex d -dimer assay safely eliminates the need for further testing in patients with low or moderate pretest probability of DVT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
108
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(111 citation statements)
references
References 40 publications
1
108
2
Order By: Relevance
“…4 The results and inclusion and exclusion criteria have been reported previously. 4 All patients underwent a sequential diagnostic investigation, consisting of clinical probability assessment using the Wells rule 13 and a quantitative latex D-dimer test (MDA D-Dimer assay, bioMérieux, Inc.).…”
Section: Cohortmentioning
confidence: 99%
See 2 more Smart Citations
“…4 The results and inclusion and exclusion criteria have been reported previously. 4 All patients underwent a sequential diagnostic investigation, consisting of clinical probability assessment using the Wells rule 13 and a quantitative latex D-dimer test (MDA D-Dimer assay, bioMérieux, Inc.).…”
Section: Cohortmentioning
confidence: 99%
“…4 The results and inclusion and exclusion criteria have been reported previously. 4 All patients underwent a sequential diagnostic investigation, consisting of clinical probability assessment using the Wells rule 13 and a quantitative latex D-dimer test (MDA D-Dimer assay, bioMérieux, Inc.). DVT was ruled out based on: (i) a non-high clinical probability in combination with a normal D-dimer test result or (ii) a normal (repeated) CUS result in patients with a high clinical probability of DVT or an abnormal D-dimer test result -CUS was repeated in patients with normal results on CUS at presentation on days 6 to 8 and days 13-15.…”
Section: Cohortmentioning
confidence: 99%
See 1 more Smart Citation
“…Table S1 lists the 21 diagnostic algorithms evaluated with this model. [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] This article focuses on the identifi cation of optimal strategies for the diagnosis of clinically suspected DVT in adults. Consecutive sections of this chapter concentrate on fi rst DVT, recurrent DVT, upper extremity DVT, and DVT during pregnancy.…”
mentioning
confidence: 99%
“…Studies in patients with a suspected first episode of venous thromboembolism have shown that some of these assays have high sensitivity for acute DVT or pulmonary embolism (11). D-dimer has been used safely as an exclusion test in patients presenting with their first episode of DVT (12)(13)(14). The sensitivity of the STA-Liatest D-di (Diagnostica Stago, Asnieres-sur-Seine, France, and Parsippany, New Jersey) has been reported to be 96% to 100% in patients with suspected first-episode DVT or symptomatic pulmonary embolism (15,16).…”
Section: Conclusion-measurement Of Plasmamentioning
confidence: 99%